61.5k views
4 votes
X^2 - 36 = 0.

Factor using the difference squares. Then solve the equation using the Zero Product Peoperty. Write your answer in set notation.

X^2 - 36 = 0. Factor using the difference squares. Then solve the equation using the-example-1
User Shaswata
by
5.2k points

1 Answer

6 votes

Answer:

(x+6)(x−6)=0

x=-6 or x=6

Explanation:

X^2 - 36 = 0

Solve by Square Root

add 36 both sides

x^2−36+36=0+36

x^2=36

square root

x=±√36

x=6 or x=−6

You can do that or for 2nd option

Solve by factoring

x^2-36=0

(x+6)(x−6)=0

Set factors equal to 0

x+6=0 or x−6=0

x=-6 or x=6

PLEASE NOTE: 36 is the square of 6

and

x2 is the square of x1

User Mark Simpson
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.